Effect of calmodulin on the structural state of photoreceptor membranes and rhodopsin-containing phospholipid vesicles. - Volotovski, I; Ryba, N; Watts, A (1985)
The effect of calmodulin on the order of lipids in rhodopsin-free and rhodopsin-containing membranes has been studied using spin-label electron spin resonance methods. Calmodulin, up to 10(-6)M, did not change the measured order of lipids in bilayer membranes containing only rhodopsin. However, for bovine rod outer segment disc membranes, which contain rhodopsin and other proteins, calmodulin induced a significant concentration and temperature dependent increase in the order of the membrane lipids. This suggests that the site of calmodulin binding is remote from rhodopsin itself, and the nature of the binding appears to be a membrane surface phenomenon.